A cyclodextrin derivative modified lead-free double perovskite degradable composite film and its bacterial imaging and photodynamic antibacterial applications
Patent Information
- Application Number
- CN202611128364.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
AI Technical Summary
本发明可克服目前无铅双钙钛矿材料存在环境稳定性不足、缺乏被细菌识别的能力以及难以同时兼顾成像、抗菌功能和生物安全性等问题
本发明公开了一种环糊精衍生物修饰可降解无铅双钙钛矿复合膜,其制备方法为首先采用湿化学法制备无铅双钙钛矿发光材料(如Sb3+/Bi3+共掺杂Cs2NaInCl6);随后利用环糊精衍生物对无铅双钙钛矿进行表面修饰,通过氢键、卤素键及配位作用构建稳定的表面锚定结构;之后再将修饰后的无铅双钙钛矿均匀分散于可生物降解聚合物(如PCL)溶液中,并通过涂覆技术成膜,即获得大面积柔性复合膜。本发明的制备方法具有原料来源广泛、制备工艺简单、成膜过程可控、重复性高以及易于规模化生产等优点;通过环糊精衍生物表面修饰与聚合物封装协同作用,还可显著提高无铅双钙钛矿材料的发光性能、水环境稳定性、长期储存稳定性以及生物安全性,并赋予材料良好的机械柔性和可加工性能。同时,所制得的复合膜可实现细菌单双光子成像、光动力抗菌及感染诊疗一体化,该复合膜能够被细菌主动识别和摄取,无需额外引入靶向配体即可实现细菌荧光标记,并兼具近红外双光子成像能力和光动力抗菌功能。此外,可生物降解聚合物封装层可在生物酶作用下逐渐降解,具有良好的生物安全性和环境友好性,为无铅钙钛矿材料在生物医用领域的应用提供了新的技术方案。
Smart Images

Figure CN122958732A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photodynamic therapy technology, specifically relating to a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane and its application in bacterial imaging and photodynamic antibacterial activity. Background Technology
[0002] With the rapid development of bioimaging technology, fluorescence imaging technology, characterized by high sensitivity, high resolution, and real-time visualization, has attracted widespread attention in fields such as pathogen detection, cell tracing, biosensing, and disease diagnosis. Especially in bacterial imaging, the development of novel fluorescent materials that combine high luminescence performance, high stability, and targeted recognition capabilities is of great significance for achieving rapid detection and precise localization of pathogens.
[0003] In recent years, metal halide perovskite materials have shown broad application prospects in fields such as light-emitting devices, display lighting, solar cells, bioimaging, and optical sensing due to their advantages such as high luminous efficiency, tunable emission wavelength, narrow half-maximum width at half-maximum (HWHM), excellent two-photon absorption performance, simple fabrication process, and low cost. Among them, lead-free double perovskite materials retain the excellent optical properties of traditional perovskites while avoiding the potential biotoxicity caused by lead, making them a promising new type of light-emitting material.
[0004] However, lead-free double perovskite materials still have certain limitations. On the one hand, the material surface contains a large number of uncoordinated ions and structural defects, which easily lead to non-radiative recombination processes, thereby reducing luminescence efficiency. On the other hand, the materials are susceptible to structural degradation due to moisture, oxygen, and external environmental factors, resulting in a decrease in luminescence performance. Furthermore, most existing bacteria lack the ability to actively recognize lead-free double perovskite materials, making it difficult to achieve accurate labeling and imaging of bacteria and other microorganisms. In addition, most perovskite materials exist in powder form, which presents problems such as inconvenience in handling, insufficient mechanical stability, and difficulty in recycling during practical biological applications.
[0005] To improve the stability and application performance of perovskite materials, researchers typically employ methods such as surface ligand modification, polymer encapsulation, and surface defect passivation. Among these, cyclodextrin supramolecular compounds possess excellent biocompatibility and abundant hydroxyl functional groups, enabling them to form stable interactions with inorganic material surfaces. Furthermore, the cyclodextrin structure can be recognized by the sugar transport systems on some bacterial surfaces, thus potentially endowing materials with targeted bacterial uptake capabilities. In addition, biodegradable polymers (such as polycaprolactone) exhibit good mechanical properties, biocompatibility, and degradation performance, showing broad application prospects in the field of biomedical materials.
[0006] Currently, no research has combined cyclodextrin derivative surface modification, lead-free double perovskite luminescent systems, and biodegradable polymer encapsulation technology to prepare a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite film that simultaneously possesses bacterial targeted imaging, two-photon absorption, and photodynamic antibacterial properties. Therefore, developing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite film with excellent luminescent performance, excellent environmental stability, bacterial targeted recognition ability, and biodegradability is of great significance for promoting the application of lead-free perovskite materials in the fields of bioimaging and photodynamic therapy. Summary of the Invention
[0007] To overcome the shortcomings of the prior art, this invention provides a lead-free double perovskite composite film with bacterial recognition capability, excellent luminescence performance, and two-photon absorption capability, and its applications in bacterial fluorescence imaging, two-photon bioimaging, and photodynamic antibacterial applications. Specifically, this invention provides a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite film, comprising a lead-free double perovskite luminescent material, a cyclodextrin derivative, and a biodegradable polymer matrix. This composite film combines a synergistic strategy of cyclodextrin derivative surface modification and biodegradable polymer encapsulation, improving the luminescence performance, environmental stability, and biosafety of the lead-free double perovskite while endowing the material with bacterial targeted recognition capability, achieving bacterial fluorescence imaging and photodynamic antibacterial functions, showing significant application prospects in the fields of bacterial imaging and photodynamic antibacterial applications. This invention overcomes the problems of insufficient environmental stability, lack of bacterial recognition capability, and difficulty in simultaneously achieving imaging, antibacterial functions, and biosafety in current lead-free double perovskite materials.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane, the method comprising the following steps: S1. According to the stoichiometric ratio of lead-free double perovskite A2M1M2X6, weigh source A, source M1, source M2, and source X and add them to the aqueous system. Add cyclodextrin derivative and mix thoroughly. Through in-situ reaction, the cyclodextrin derivative and lead-free double perovskite undergo interfacial assembly to obtain lead-free double perovskite material A2M1M2X6 modified with cyclodextrin derivative. Where A is selected from Cs + M1 is selected from Na + Ag + K + At least one of them; M2 is selected from Bi 3+ Sb 3+ In 3+ Er 3+ At least one of them; X is selected from Cl - , Br- At least one of them; The cyclodextrin derivative is selected from at least one of the substituted derivatives of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and the aqueous phase system is a single solvent system of water and hydrochloric acid or a mixed solvent system of both. S2. Dissolve the biodegradable polymer in an organic solvent to obtain a polymer solution; The polymers include at least one of the following: polycaprolactone (PCL), polylactic acid (PLA), polyglycolic acid (PGA), polylactic acid-glycolic acid copolymer (PLGA), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), polyhexyl succinate (PBSA), polybutylene adipate / terephthalate (PBAT), polylactic acid-caprolactone copolymer (PLCL), polytrimethylene carbonate (PTMC), polydioxanone (PPDO), polyglycolic acid-caprolactone copolymer (PGCL), polyhydroxybutyrate (PHB), polyhydroxyvalerate (PHV), polyhydroxybutyrate-hydroxyvalerate copolymer (PHBV), polyhydroxyalkanoate (PHA), gelatin, chitosan, sodium alginate, hyaluronic acid, and silk fibroin. S3. The lead-free double perovskite material A2M1M2X6 modified with cyclodextrin derivatives described in S1 is mixed with the polymer solution described in S2 to obtain a film-forming precursor solution, which is then coated to form a film, thereby obtaining a biodegradable composite film modified with cyclodextrin derivatives.
[0009] This invention discloses a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane. The composite membrane uses cyclodextrin derivative-modified lead-free double perovskite material as the functional component, dispersed in a biodegradable polymer matrix, and prepared through a coating process. The cyclodextrin derivative modification enhances the luminescence performance and environmental stability of the lead-free double perovskite material, and endows bacteria with the ability to absorb it. Simultaneously, the composite membrane exhibits excellent luminescence performance, long-term storage stability, bioenvironmental stability, and biodegradability, enabling single-photon and two-photon fluorescence imaging of bacteria. Under illumination, it generates reactive oxygen species, achieving photodynamic antibacterial effects against bacteria. Furthermore, the composite membrane has a simple preparation process, low cost, and is easy to scale up, showing significant application prospects in bacterial imaging and photodynamic antibacterial applications, and can be used in bacterial detection, bioimaging, and bacterial diagnosis and treatment.
[0010] Preferably, the cyclodextrin derivative is selected from at least one of hydroxypropyl cyclodextrin, carboxymethyl cyclodextrin, halogenated cyclodextrin, or aminocyclodextrin, such as octa(6-bromo-6-deoxy)γ-cyclodextrin. Cyclodextrin derivatives can improve the luminescent properties and environmental stability of lead-free double perovskite materials.
[0011] Preferably, the amount of the cyclodextrin derivative added is 0.1 to 50 wt% of the mass of the lead-free double perovskite material.
[0012] Preferably, the polymer is biodegradable polycaprolactone.
[0013] Preferably, the ratio of the lead-free double perovskite material A2M1M2X6 modified with the cyclodextrin derivative to the polymer solution is 5-1000 mg: 1-100 mL, and the mass concentration of the polymer solution is 10%-25%.
[0014] Preferably, the cyclodextrin derivative-modified lead-free double perovskite material A2M1M2X6 is selected from Sb 3+ and Bi 3+ Co-doped Cs2NaInCl6-based lead-free double perovskite.
[0015] Preferably, the organic solvent includes one or more of the following: alkanes (cyclohexane, n-hexane, n-pentane, n-octane, n-tetradecane, etc.), aromatic hydrocarbons (benzene, toluene, xylene, etc.), halogenated hydrocarbons (carbon tetrachloride, chloroform, dichloromethane, dichloroethane, etc.), 2-methyltetrahydrofuran (MeTHF), tetrahydrofuran (THF), N-methylpyrrolidone (NMP), 2-methoxyethanol (2-ME), γ-butyrolactone (GBL), acetonitrile (ACN), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).
[0016] More preferably, the organic solvent includes at least one selected from cyclohexane, n-hexane, n-pentane, n-octane, n-tetradecane, benzene, toluene, xylene, carbon tetrachloride, chloroform, dichloromethane, dichloroethane, 2-methyltetrahydrofuran, tetrahydrofuran, N-methylpyrrolidone, 2-methoxyethanol, γ-butyrolactone, acetonitrile, dimethylformamide, and dimethyl sulfoxide.
[0017] Preferably, the coating film formation method includes blade coating, drop coating, spin coating, spray coating, inkjet printing, and dip coating.
[0018] More preferably, the coating film formation method is selected from the blade coating method. That is, the film is formed by blade coating technology, in which a polymer dispersion containing cyclodextrin derivative modified lead-free double perovskite material is uniformly spread on the substrate surface, and a blade is moved in a fixed direction under a preset gap condition to form a uniform liquid film. After the solvent evaporates, the biodegradable composite film of cyclodextrin derivative modified lead-free double perovskite is obtained.
[0019] Furthermore, the coating method includes, but is not limited to, manual coating, automatic coating, precision blade coating, and roll-to-roll continuous coating processes.
[0020] Furthermore, the coating substrate is one or more of glass, quartz, metal, polyethylene terephthalate (PET), polyimide (PI), or other flexible substrates.
[0021] Furthermore, during the coating process, the gap between the scraper and the substrate is 10–2000 μm, the coating speed is 0.1–100 mm / s, the ambient temperature is 10–80 ℃, and the relative humidity is 10%–80%.
[0022] Preferably, after coating, the film can only be formed after the solvent evaporates. The solvent evaporation is one or more of the following: natural evaporation at room temperature, heating evaporation, vacuum drying, or drying evaporation under an inert atmosphere. The drying temperature is 20-100 °C, and the drying time is 0.1-48 h.
[0023] Preferably, the thickness of the cyclodextrin derivative-modified lead-free double perovskite biodegradable composite film is 1 μm to 5 mm.
[0024] The second aspect of the present invention also provides a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane prepared by the preparation method described in the first aspect.
[0025] The third aspect of this invention also provides the application of the cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane described in the second aspect in the preparation of bacterial imaging agents and / or photodynamic antibacterial diagnostic and therapeutic formulations.
[0026] The cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane has the ability to be targeted and taken up by bacteria, single-photon imaging capability, two-photon imaging capability, and photodynamic antibacterial capability, and can be used in the fields of bacterial fluorescence imaging, two-photon bioimaging, and photodynamic antibacterial.
[0027] Preferably, the bacterial imaging uses a near-infrared laser as the excitation source to perform two-photon fluorescence imaging on bacteria that have taken up the cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane; the excitation wavelength of the near-infrared laser is 700–1000 nm.
[0028] Preferably, photodynamic antibacterial treatment employs light-induced generation of reactive oxygen species (such as singlet oxygen, superoxide anion radicals, or hydroxyl radicals) in the lead-free double perovskite biodegradable composite membrane modified by the cyclodextrin derivative to achieve bacterial inactivation. The light irradiation is ultraviolet light, near-ultraviolet light, or visible light irradiation.
[0029] Preferably, the bacteria include Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and other pathogenic microorganisms.
[0030] Compared with the prior art, the beneficial effects of the present invention are: This invention discloses a cyclodextrin derivative-modified biodegradable lead-free double perovskite composite film, the preparation method of which involves first preparing a lead-free double perovskite luminescent material (such as Sb) using a wet chemical method. 3+ / Bi 3+ The process involves co-doping with Cs₂NaInCl₆, followed by surface modification of the lead-free double perovskite using cyclodextrin derivatives. A stable surface anchoring structure is constructed through hydrogen bonding, halogen bonding, and coordination. The modified lead-free double perovskite is then uniformly dispersed in a biodegradable polymer (such as PCL) solution and coated to form a large-area flexible composite film. This invention offers advantages such as wide availability of raw materials, simple preparation process, controllable film formation, high repeatability, and ease of large-scale production. The synergistic effect of cyclodextrin derivative surface modification and polymer encapsulation significantly improves the luminescence performance, aqueous stability, long-term storage stability, and biosafety of the lead-free double perovskite material, while also imparting good mechanical flexibility and processability. Furthermore, the resulting composite film enables integrated bacterial single- and two-photon imaging, photodynamic antibacterial activity, and infection diagnosis and treatment. This composite film can be actively recognized and taken up by bacteria, achieving bacterial fluorescent labeling without the need for additional targeting ligands, and possesses both near-infrared two-photon imaging capabilities and photodynamic antibacterial functions. Furthermore, the biodegradable polymer encapsulation layer can gradually degrade under the action of biological enzymes, exhibiting good biosafety and environmental friendliness, and providing a new technical solution for the application of lead-free perovskite materials in the biomedical field.
[0031] Specifically, the present invention has the following advantages: (1) The present invention uses cyclodextrin derivatives to modify the surface of lead-free double perovskite, and achieves effective passivation and stable anchoring of the perovskite surface through multiple interactions, significantly reducing the surface defect density and improving the luminescent performance and environmental stability of the material.
[0032] (2) The present invention utilizes the characteristic that cyclodextrin derivatives are glucose derivatives and uses them as a carbon source required for bacterial growth. Based on this characteristic, bacteria can specifically recognize and actively take up the composite membrane material of the present invention, thereby realizing the active uptake of the composite membrane by bacteria and the internal fluorescent labeling of bacteria, which can be used for pathogen detection and bacterial localization imaging.
[0033] (3) The lead-free double perovskite material used in this invention can avoid the heavy metal toxicity problem that may be caused by traditional lead-based perovskites. While maintaining excellent luminescence performance, it improves the biosafety of the material and is more suitable for applications in the field of bioimaging.
[0034] (4) The composite membrane prepared by this invention has both single-photon fluorescence imaging and two-photon fluorescence imaging capabilities. Among them, the two-photon imaging uses near-infrared light excitation, which has the advantages of large tissue penetration depth, small background interference and low light damage, and can meet the needs of deep biological imaging.
[0035] (5) The composite membrane prepared by the present invention can effectively generate reactive oxygen species under light conditions and has good photodynamic antibacterial properties, thereby realizing multi-functional integration such as bacterial recognition, fluorescence imaging and light-controlled antibacterial.
[0036] (6) The present invention uses a biodegradable polymer as the encapsulation substrate, which helps to reduce the potential environmental and biosafety risks caused by long-term material residue.
[0037] (7) The composite membrane described in this invention has a simple preparation process, a wide range of raw material sources, good repeatability, and is easy to scale up. It can be widely used in fields such as bacterial imaging, photodynamic antibacterial and intelligent diagnosis and treatment. Attached Figure Description
[0038] Figure 1 XPS spectra of lead-free double perovskite materials before and after modification with cyclodextrin derivatives; a is the XPS spectrum of Cl 2p orbital, b is the XPS spectrum of Br 3d orbital, c is the XPS spectrum of Na 1s orbital, and d is the XPS spectrum of In 3d orbital. Figure 2 FTIR spectra of lead-free double perovskite materials before and after modification with cyclodextrin derivatives; Figure 3 Fluorescence spectra of different regions of a lead-free double perovskite biodegradable composite film modified with cyclodextrin derivatives; Figure 4 Cross-sectional elemental energy dispersive spectroscopy (EDS) analysis of a lead-free double perovskite biodegradable composite membrane modified with cyclodextrin derivatives; Figure 5 Fluorescence quantum yield of lead-free double perovskite biodegradable composite films modified with cyclodextrin derivatives; Figure 6 Photoluminescence intensity tracking diagram of lead-free double perovskite biodegradable composite film modified with cyclodextrin derivatives under normal storage conditions; Figure 7 Photoluminescence intensity tracking diagram of a lead-free double perovskite biodegradable composite membrane modified with cyclodextrin derivatives under aqueous storage; Figure 8 The photoluminescence spectrum of the lead-free double perovskite biodegradable composite film modified with cyclodextrin derivatives under ultraviolet light irradiation conditions changes over time (a) and the corresponding photoluminescence intensity changes over time (b). Figure 9 Single-photon and two-photon imaging effects of bacteria on a lead-free double perovskite biodegradable composite membrane modified with cyclodextrin derivatives; Figure 10 Photodynamic antibacterial effect of lead-free double perovskite biodegradable composite membrane modified with cyclodextrin derivatives; Figure 11This is a photograph of a lead-free double perovskite biodegradable composite membrane modified with cyclodextrin derivatives undergoing gradual degradation under the action of lipase. Detailed Implementation
[0039] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0040] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0041] This invention proposes a biodegradable lead-free double perovskite integrated diagnostic and therapeutic composite membrane modified with cyclodextrin derivatives, possessing bacterial recognition capabilities, excellent luminescence performance, and two-photon absorption capabilities. This composite membrane uses lead-free double perovskite as its luminescent core, and a stable composite structure is synergistically constructed through surface modification with cyclodextrin derivatives and encapsulation with biodegradable polymers. While maintaining excellent luminescence performance, it also significantly improves the material's environmental stability and biosafety. This composite membrane can be actively recognized and taken up by bacteria, achieving bacterial fluorescent labeling without the need for additional targeting ligands. It generates bright and stable fluorescence signals under both single-photon and two-photon excitation conditions, enabling bacterial fluorescence imaging and deep tissue two-photon imaging. Simultaneously, under illumination, this composite membrane can effectively generate reactive oxygen species, exerting photodynamic antibacterial therapeutic effects, thus achieving integrated bacterial recognition, fluorescence imaging, and photocontrolled therapy. Furthermore, the polymer encapsulation layer can gradually degrade under the action of biological enzymes, which helps reduce the potential risks of long-term material residue and improves the material's biocompatibility and environmental friendliness.
[0042] Furthermore, the composite membrane provided by this invention has the advantages of simple preparation process, readily available raw materials, high repeatability, and large-scale production, and can be widely used in fields such as pathogen detection, bacterial fluorescence imaging, two-photon bioimaging, photodynamic antibacterial, and integrated diagnosis and treatment of infection.
[0043] The following examples, 1-6, further illustrate the process of modifying lead-free double perovskite biodegradable composite membranes with cyclodextrin derivatives constructed according to the present invention and their application in bacterial imaging, photodynamic antibacterial activity, and infection diagnosis and treatment.
[0044] Example 1: A method for preparing lead-free double perovskite materials modified with cyclodextrin derivatives The specific preparation method includes the following steps: (1) Weigh 9 mmol NaCl, 1.988 mmol InCl3, and 4 mmol CsCl, and dissolve them in 1.5 mL, 1 mL, and 1 mL of ultrapure water, respectively. After thorough stirring, the concentrations obtained are 6 mol·L⁻¹. -1 1.988 mol·L -1 4 mol·L -1 NaCl, InCl3, and CsCl precursor solutions; (2) Weigh 0.2 mmol SbCl3 and 0.2 mmol BiCl3, dissolve them in 2 mL and 2 mL of 37 wt% HCl respectively, and stir thoroughly to obtain a concentration of 0.1 mol·Lmol·L -1 SbCl3 and BiCl3 precursor solutions; (3) Mix 1.5 mL of NaCl precursor solution with 1 mL of InCl3 precursor solution, add 20 mg of octakis-(6-bromo-6-deoxy)-γ-cyclodextrin powder (CDBr), then add 200 μL of SbCl3 precursor solution and 20 μL of BiCl3 precursor solution, and finally quickly inject 1 mL of CsCl precursor solution. Centrifuge at 2000 rpm for 2 minutes, remove the supernatant, and vacuum dry to obtain lead-free double perovskite DP@CDBr (SbCl3) before and after cyclodextrin modification. 3+ / Bi 3+ Co-doped Cs2NaInCl6 double perovskite (DP) material (CDBr modified).
[0045] Figure 1 and Figure 2 The X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) spectra of the lead-free double perovskite DP and DP@CDBr materials before and after modification with the cyclodextrin derivative CDBr are shown. FTIR results show that, compared to the unmodified sample, both the OH vibrational peak and the C-Br vibrational peak associated with the cyclodextrin derivative in DP@CDBr shift, indicating a strong interfacial interaction between the cyclodextrin derivative and the lead-free double perovskite, altering the surface chemical environment. XPS results show changes in the binding energies of Cl 2p, Br 3d, Na 1s, and In 3d, further demonstrating the presence of hydrogen bonds, halogen bonds, and coordination bonds between the cyclodextrin derivative and the lead-free double perovskite surface, altering the electron density around the elements. These results collectively demonstrate that the cyclodextrin derivative was successfully modified onto the lead-free double perovskite surface and exhibited strong chemical interactions, resulting in the cyclodextrin derivative-modified lead-free double perovskite material DP@CDBr.
[0046] Example 2: A method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane (1) Prepare a 20% PCL (polycaprolactone) / TL (toluene) polymer solution, then add 100 mg of the powder prepared in Example 1 to 4 mL of PCL polymer solution and mix thoroughly at 60 °C to obtain a suspension. (2) The above suspension was deposited on the glass substrate by blade coating to form a 65 μm thick film, thus completing the deposition process of the glass substrate. During the deposition process, the ambient temperature was 20℃, the relative humidity was 50±5%, an automatic blade coating machine was used, the blade slit width was set to 1500 μm, the coating speed was set to 7 mm / s, and the substrate temperature was controlled at 15~20℃. After deposition, the film was left to stand for 3 hours until the solvent completely evaporated, and then the film was peeled off from the substrate to obtain a cyclodextrin derivative modified lead-free double perovskite biodegradable composite film.
[0047] The emission spectra of nine different regions of the prepared cyclodextrin derivative-modified lead-free double perovskite biodegradable composite film were measured using fluorescence spectroscopy. The results are as follows: Figure 3 As shown in the figure, all test areas exhibited essentially uniform emission spectra, indicating that the prepared composite film possesses good luminescence uniformity. The composite film was characterized using energy-dispersive X-ray spectroscopy (EDS), and the results are as follows: Figure 4 As shown in the figure, all constituent elements are uniformly distributed within the film, indicating that the cyclodextrin derivative-modified lead-free double perovskite material can be uniformly dispersed in the polymer matrix. The fluorescence quantum yield of the composite film was determined using the integrating sphere method, and the results are as follows. Figure 5 As shown, its fluorescence quantum yield reached 99.5%, indicating that the prepared composite film has excellent luminescent properties. Furthermore, the stability of the prepared composite film was tested. The results showed that after storage in a normal environment (relative humidity 40–60%) for 9 months, its emission spectrum and fluorescence intensity remained basically stable. Figure 6 After soaking in aqueous solution for 24 h, the two characteristic emission peaks still maintained 84.6% and 47.8% of their initial intensities, respectively. Figure 7 After continuous ultraviolet light (light power approximately 11 mW) irradiation for 25 minutes, the fluorescence intensity still maintained more than 95% of the initial value. Figure 8 The above results demonstrate that the cyclodextrin derivative-modified lead-free double perovskite composite biodegradable membrane prepared in this invention exhibits excellent luminescent properties and environmental stability.
[0048] Example 3: Application of composite membrane in fluorescence imaging of Escherichia coli The specific preparation method includes the following steps: (1) The culture medium containing 10 g / L tryptone, 10 g / L NaCl and 5 g / L yeast extract was autoclaved (0.5 MPa, 121°C, 15 minutes), and the pH was adjusted to 7.4±0.1. *Escherichia coli* (BNCC133264, BeNa Culture Collection) was first cultured for 24 hours, followed by three repeated subcultures in sealed serum bottles with a 10% inoculum to eliminate initial culture stress and obtain a stable bacterial population. During each subculture, the culture bottles were placed in an incubator and shaken at 120 rpm, with the temperature controlled at 37±0.5 °C, for 24 hours.
[0049] (2) Add 2 mL of solution with a concentration of approximately 10 9 A lead-free double perovskite biodegradable composite membrane was modified with approximately 5.0 ± 0.1 mg of cyclodextrin derivative in a CFU / mL E. coli suspension and cultured for 10 hours to promote bacterial contact and binding to the composite membrane, followed by fluorescence imaging. Ten hours after adding the composite membrane, a microbial sample (0.2 mL supernatant) was collected from each culture flask.
[0050] (3) Use a confocal laser scanning microscope to observe Escherichia coli and evaluate the effect of fluorescent labeling.
[0051] Figure 9 Confocal laser scanning microscopy (CLSM) images obtained in bright-field mode (grayscale image) and fluorescence mode using 405 nm single-photon excitation (1PEF, pseudo-yellow) and 750 nm two-photon excitation (2PEF, pseudo-yellow), respectively. The results show that after treatment with the lead-free double perovskite composite membrane modified with the cyclodextrin derivative, bacterial samples exhibited significant fluorescence signals in both 1PEF and 2PEF imaging modes, indicating that the composite membrane can be effectively taken up by bacteria and achieve fluorescent labeling.
[0052] The fact that a clear two-photon fluorescence image can still be obtained under 750 nm near-infrared excitation indicates that the composite film prepared in this invention has good two-photon fluorescence imaging capability and can be used for two-photon fluorescence imaging detection of bacteria.
[0053] Example 4: Application of composite membrane in photodynamic killing of Escherichia coli The specific preparation method includes the following steps: (1) After autoclaving (0.5 MPa, 121°C, 15 minutes) the culture medium containing 10 g / L tryptone, 10 g / L sodium chloride and 5 g / L yeast extract, the pH was adjusted to 7.4±0.1. The bacteria were first cultured for 24 hours, and then passaged three times in sealed serum bottles with a 10% inoculum to eliminate initial culture stress and obtain a stable bacterial population. During each passage, the culture bottle was placed in an incubator and shaken at 120 rpm, with the temperature controlled at 37±0.5 °C, for 24 hours.
[0054] (2) Lead-free double perovskite biodegradable composite membranes modified with different masses of cyclodextrin derivatives were dispersed in Escherichia coli suspension and subjected to broadband light irradiation (400–800 nm, light intensity approximately 127 mW·cm). -2 The samples were co-cultured for 60 minutes, with a parallel experiment conducted in the dark serving as a control group. The treated suspension was serially diluted, inoculated onto agar plates, and incubated overnight. Antimicrobial activity was quantified by counting the colony units (CFU) formed.
[0055] Figure 10 The antibacterial effects of different concentrations of the composite membrane on *Escherichia coli* under light and dark conditions were demonstrated. The results showed that under light conditions, the number of surviving bacteria gradually decreased with increasing composite membrane concentration. Without the composite membrane, the bacterial concentration was approximately 8.8 × 10⁻⁶. 8 CFU / mL; when the composite membrane concentration was 5, 10, and 15 mg / mL, the bacterial concentration decreased to approximately 7.5 × 10⁻⁶. 8 6.1 × 10 8 and 5.4 × 10 8 CFU / mL. Based on the colony count results, the corresponding antibacterial efficiencies were 14.8%, 30.7%, and 38.6%, respectively. Simultaneously, under dark conditions, the number of surviving bacteria in each experimental group did not change significantly, indicating that the antibacterial effect of this composite membrane mainly originates from photoinduced reactive oxygen species. These results demonstrate that the cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane prepared in this invention possesses concentration-dependent photodynamic antibacterial activity. Its antibacterial effect can be effectively controlled by adjusting the amount of composite membrane used, and it can be applied to the fields of bacterial photodynamic killing and related integrated diagnosis and treatment.
[0056] Example 5: Evaluation of the biodegradability of the composite membrane The specific preparation method is as follows: A lipase / PBS solution with a concentration of 5 mg / mL was prepared, and a lead-free double perovskite membrane modified with cyclodextrin derivative was immersed in the lipase / PBS solution. The membrane was then placed in an incubator and shaken at 120 rpm, with the temperature controlled at 37±0.5 ℃.
[0057] Figure 11 The degradation process of a cyclodextrin derivative-modified lead-free double perovskite composite membrane in lipase / PBS solution was demonstrated. With prolonged degradation time, the composite membrane gradually underwent structural damage and size reduction, with the PCL polymer matrix essentially completely degraded within 3 days. These results indicate that the degradable polymer matrix in the composite membrane prepared by this invention can gradually degrade under suitable conditions, promoting a reduction in the structural integrity of the composite membrane, thereby potentially reducing the long-term impact of material residues and improving its safety for biological applications. Simultaneously, the internally loaded lead-free double perovskite crystals are gradually released from the polymer network or dispersed into the external environment. Due to the lead-free component design and the cyclodextrin derivative surface modification strategy, the released crystalline material exhibits low biotoxicity and risk in the environment.
[0058] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane, characterized in that, Includes the following steps: S1. According to the stoichiometric ratio of lead-free double perovskite A2M1M2X6, weigh source A, source M1, source M2, and source X and add them to the aqueous system. Add cyclodextrin derivative and mix thoroughly. Through in-situ reaction, the cyclodextrin derivative and lead-free double perovskite undergo interfacial assembly to obtain lead-free double perovskite material A2M1M2X6 modified with cyclodextrin derivative. Where A is selected from Cs + M1 is selected from Na + Ag + K + At least one of them; M2 is selected from Bi 3+ Sb 3+ In 3+ Er 3+ At least one of them; X is selected from Cl - , Br - At least one of them; The cyclodextrin derivative is selected from at least one of the substituted derivatives of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and the aqueous phase system is a single solvent system of water and hydrochloric acid or a mixed solvent system of both. S2. Dissolve the biodegradable polymer in an organic solvent to obtain a polymer solution; The polymer comprises at least one of the following: polycaprolactone, polylactic acid, polyglycolic acid, polylactic acid-glycolic acid copolymer, polyhydroxy fatty acid ester, polybutylene succinate, polyhexyl succinate, polybutylene adipate / terephthalate, polylactic acid-caprolactone copolymer, polytrimethylene carbonate, polydioxanone, polyglycolic acid-caprolactone copolymer, polyhydroxybutyrate, polyhydroxyvalerate, polyhydroxybutyrate-hydroxyvalerate copolymer, polyhydroxy fatty acid ester, gelatin, chitosan, sodium alginate, hyaluronic acid, and silk fibroin. S3. The lead-free double perovskite material A2M1M2X6 modified with cyclodextrin derivatives described in S1 is mixed with the polymer solution described in S2 to obtain a film-forming precursor solution, which is then coated to form a film, thereby obtaining a biodegradable composite film modified with cyclodextrin derivatives.
2. The method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane according to claim 1, characterized in that, The cyclodextrin derivative is selected from at least one of hydroxypropyl cyclodextrin, carboxymethyl cyclodextrin, halocyclodextrin, or aminocyclodextrin; the amount of the cyclodextrin derivative added is 0.1 to 50 wt% of the mass of the lead-free double perovskite material.
3. The method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane according to claim 1, characterized in that, The ratio of the lead-free double perovskite material A2M1M2X6 modified with the cyclodextrin derivative to the polymer solution is 5-1000 mg: 1-100 mL, and the mass concentration of the polymer solution is 10%-25%.
4. The method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane according to claim 1, characterized in that, The cyclodextrin derivative-modified lead-free double perovskite material A2M1M2X6 is selected from Sb 3+ and Bi 3+ Co-doped Cs2NaInCl6-based lead-free double perovskite.
5. The method for preparing a cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane according to claim 1, characterized in that, The coating methods include blade coating, drop coating, spin coating, spray coating, inkjet printing, and dip coating.
6. A cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the cyclodextrin derivative modified lead-free double perovskite biodegradable composite membrane according to claim 6 in the preparation of bacterial imaging agents and / or photodynamic antibacterial diagnostic and therapeutic integrated formulations.
8. The application according to claim 7, characterized in that, Bacterial imaging uses a near-infrared laser as the excitation source to perform two-photon fluorescence imaging on bacteria that have taken up the cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane; the excitation wavelength of the near-infrared laser is 700–1000 nm.
9. The application according to claim 7, characterized in that, Photodynamic antibacterial treatment employs light-induced oxidation of the cyclodextrin derivative-modified lead-free double perovskite biodegradable composite membrane to generate reactive oxygen species, thereby achieving bacterial inactivation. The light source is ultraviolet light, near-ultraviolet light, or visible light irradiation.
10. The application according to claim 7, characterized in that, The bacteria include Escherichia coli, Staphylococcus aureus, or Pseudomonas aeruginosa.